In Vitro Antibacterial Activity of Curcumin and Protocatechuic Acid Against Extended-Spectrum β-Lactamase–Producing Klebsiella pneumoniae Isolated from Chronic Cough Sputum - Hayati, Zinatul; Iwan Tona , Azwar; Prima , Agus (Journal of Society Medicine, 2026)
Introduction: Curcumin and protocatechuic acid are naturally occurring phenolic compounds that have been investigated for their potential antimicrobial properties. Extended-spectrum beta-lactamase-producing Klebsiella pneumoniae is a major clinical concern because of the limited therapeutic options. This study aimed to isolate and identify K. pneumoniae ESBL from the sputum of patients with chronic cough and evaluate the antibacterial effects of curcumin and protocatechuic acid. Methods: A laboratory-based experimental study was conducted using sputum specimens from 100 patients with chronic cough. Bacterial isolation and identification were performed using standard microbiological procedures, followed by the confirmation of ESBL production. The antibacterial activities of curcumin and protocatechuic acid at 25 %, 50 %, and 75% concentrations were assessed using the disc diffusion method. Statistical analyses were performed using one-way analysis of variance (ANOVA) followed by post hoc testing. Results: Nine bacterial species were identified in the sputum samples. Klebsiella pneumoniae accounted for 27.5% of isolates, of which 7.5% were confirmed as ESBL-producing strains. Curcumin, at all tested concentrations, produced inhibition zones of approximately 6 mm, with no statistically significant differences between the concentrations tested. In contrast, protocatechuic acid demonstrated concentration-dependent antibacterial activity, producing mean inhibition zones of 20.6, 16.0, and 10.8 mm at 25%, 50%, and 75% concentrations, respectively, with statistically significant differences. The antibacterial effect of 75% protocatechuic acid was comparable to that of 10 µg meropenem. Conclusion: Curcumin showed no significant antibacterial activity against ESBL-producing K. pneumoniae, while protocatechuic acid exhibited significant and concentration-dependent inhibitory effects. These findings suggest that protocatechuic acid is a potential natural antibacterial agent against ESBL-producing K. pneumoniae.